A Triad of Defenses to Mitigate Poisoning Attacks in Federated Learning - Mazetto, Blenda Oliveira; Zarpelão, Bruno Bogaz (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
Federated learning (FL) enables the training of machine learning models on decentralized data, potentially improving data privacy. However, the FL distributed architecture is vulnerable to poisoning attacks. In this paper, we propose an FL method capable of mitigating these attacks through a triad of defense strategies: organizing clients into groups, checking the local performance of global models during training, and using a voting scheme during the inference phase. The proposed approach first divides the clients into randomly sampled groups, with each group generating a different global model. Each client then receives all global models and selects the one with the best predictive performance to continue training. The selected global models are updated by the clients and then submitted again to the central server, which aggregates these models. During the inference phase, each client classifies its inputs according to a majority-based voting scheme among the global models. Our experiments using the HAR and MNIST datasets show that our method can effectively mitigate poisoning attacks without compromising the global model’s results.